ROUGHNESS OF PROCESSED SURFACES UNDER ABRASIVE POLISHING - Valentin SHKURUPY (Fiabilitate şi Durabilitate)
The obtained analytical dependences for determining the basic parameters of the surface roughness during abrasive polishing are presented with modeling the cutting grains in the form of a sphere and considering the ordered arrangement of grains. It is shown that with a decrease in the thickness of the cut, the ratio of the altitude parameters of the surface roughness max Ra R / increases, reaching values of 20 ... 30 and more. This is consistent with the experimental data obtained by abrasive polishing. Consequently, the modeling of abrasive grains in the form of a sphere is more in line with the actual conditions for the formation of surface roughness in both abrasive polishing and grinding. Calculations established that the process of abrasive polishing proceeds under conditions corresponding to the transition from the cutting process to the process of friction of the grain with the material being processed. It is also shown that with the reduction of the ratio max Ra R / to 4 ... 6 (corresponding to the grinding conditions), the process of metal removal and the formation of surface roughness occurs in a stable cutting process. This establishes a close relationship of the relationship max Ra R / with the ratio of the thickness of the cut and the radius of rounding of the cutting edge of the abrasive grain. It has been experimentally established that when the ball is smoothed out, the ratio max Ra R / = 14.2, and Ra = 0.1 mkm. At fine turning with a diamond tool max Ra R / = 21.2, and Ra = 0.1 micron. When abrasive polishing max Ra R / = 30, and Ra = 0.1 micron. The obtained results of theoretical and experimental studies indicate the possibility of a significant decrease in the surface roughness in abrasive polishing, which opens up new technological possibilities for its practical use.